The Psychological Impacts of Acne - Shumaila, Naeem Soomro, Samreen Shaikh, Muneeba, Irfan Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of different category of Dermatology Life Quality Index (DLQI) in patients with Acne Vulgaris visiting to tertiary care hospital. Study Design: Descriptive Cross-Sectional Study. Place and Duration: This study was conducted at the Department of Dermatology, Shaheed Mohtarma Benazir Bhutto Medical University, Larkana, Pakistan during the period from August 23, 2019 to February 22, 2020. Materials and Methods: All patients who fulfilled the inclusion criteria and visited to SMBBMU, Larkana were included in the study. Informed consent was taken after explaining the procedure, risks and benefits of the study. In our study, patients with acne vulgaris were diagnosed on the basis of relevant clinical history and examination. Patients were asked to fill the DLQI questionnaire themselves to assess the DLQI. All the collected data were entered into the proforma attached at the end and used electronically for research purpose. Results: Mean ± SD of age was 25.4±5.2 years. Out of 343 patients, 157 (45.8%) were male and 186 (54.2%) were female. In frequency of different category of dermatology life quality index (DLQI) 44 (12.8%) patients had no effect, 105 (30.6%) had mild, 74 (21.6%) moderate effect, 86 (25.1%) had very large while 34 (9.9%) patients had extreme larger effect. Conclusion: It is to be concluded that his study showed significant impairment of QoL in acne patients. Assurance and counseling along with early treatment of acne vulgaris are important to reduce disease-related psychosocial sequelae.